2018
DOI: 10.2147/copd.s174665
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with COPD after 9 years

Abstract: BackgroundCOPD is one of the leading causes of morbidity and mortality in the world; however, the most varied amounts of clinical and laboratory characteristics acts in different ways in the mortality among over time. Therefore, this study aimed to evaluate the predictors of mortality in patients with COPD after 9 years.Patients and methodsOne hundred and thirty-three patients with COPD were assessed at baseline by spirometry, pulse oximetry (SpO2), body composition, intensity of dyspnea, distance walked in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…[23][24][25] Moreover, comorbidities including, eg, heart failure, low BMI, and depression have all been associated with an increased risk of dying from COPD. [26][27][28][29] In order to obtain a higher precision, composites such as the BODE and ADO have been created, with proved predictive value in certain studies. 2,7,8,14,15,17,27 Many of the commonly suggested variables covary within the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] Moreover, comorbidities including, eg, heart failure, low BMI, and depression have all been associated with an increased risk of dying from COPD. [26][27][28][29] In order to obtain a higher precision, composites such as the BODE and ADO have been created, with proved predictive value in certain studies. 2,7,8,14,15,17,27 Many of the commonly suggested variables covary within the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] In order to obtain a higher precision, composites such as the BODE and ADO have been created, with proved predictive value in certain studies. 2,7,8,14,15,17,27 Many of the commonly suggested variables covary within the same patient. A person with severe COPD is likely to present with dyspnoea, as well as insufficient saturation, low FEV 1 %, and episodes of exacerbations, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Clinical variables that predict mortality are important for identifying patients at highest risk and include lung function, exacerbation burden and comorbidities. [1][2][3][4] Interestingly, when comparing mortality risk based purely on lung function and the symptoms-exacerbation risk-based Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2013 COPD classification, lung function served as a better predictor. 5 It has long been debated whether forced expiratory volume in one second (FEV 1 ) or forced vital capacity (FVC) is the best physiological prognostic measure and if the relationship between FEV 1 and mortality is due to airflow limitation or low lung volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a wide range of mortality which depends on follow-up period, for example, 16% for 90-day mortality [37], 19-26% for 1-year mortality [32,38] to 64% for 5-year mortality [38]. Due to the retrospective nature of our study, we were not able to use any indices such as BODE (Body mass index, airway Obstruction, Dyspnea, and Exercise capacity) or CCI (Charlson Comorbidity Index) to predict the mortality in COPD patients, as did other [39]. Our pre-admission data (Table 1) shows that around 50% of the patients in both groups were still smokers.…”
Section: All-cause Mortalitymentioning
confidence: 95%